Optimalisasi Penggunaan Online Marketplace Pada UMKM “Cahaya Dua Kitri Enterprise” Jelekong-Baleendah Kabupaten Bandung - Wahyuddin Bagenda; Mira Veranita; R. Oke Andikarya; Tresna Budiarti; Redi Setiyadi; Ghufran Al Fikri (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
This Community Service Activity aims to optimize the use of online marketplaces by UMKM "Cahaya Dua Kitri Enterprise," a fashion business in Jelekong, Baleendah District, Bandung Regency. With a systematic approach through observation, situation analysis, training, and evaluation, this study identified major obstacles such as lack of digital literacy, minimal marketing strategies, and limited resources. Through intensive training and mentoring, optimization efforts were made including improving the quality of digital content, utilizing marketplace promotion features, and collaborating with local communities. The results showed an increase in store visits of up to 150%, a 40% increase in sales, and an increase in positive reviews from customers. This emphasizes the importance of digitalization for UMKM to increase competitiveness and empower the local economy, while also making a real contribution to digital transformation in the UMKM sector in Indonesia.